Subsidies for intracity and intercity commuting - Rainald Borck; Matthias Wrede (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes subsidies for intracity and intercity commuting in an urban economics framework with two cities and agglomeration externalities, where workers may commute within and between cities. First, commuting subsidies serve to internalize agglomeration externalities: Intracity commuting subsidies give incentives to move to the larger city and intercity commuting subsidies make residents of the periphery commute to the core. Second, if agglomeration rents are locally captured, commuting subsidies act as a welfare enhancing transfer from the core to the periphery.
Keywords: R14; R48; 330; commuting subsidies; agglomeration externalities; intercity and intracity commuting; Pendelverkehr; Berufsverkehr; Verdichtungsverkehr; Subvention; Agglomerationseffekt; Kern-Peripherie-Beziehung; Theorie